Jael’s Syndrome – A case report (Research, Society and Development, 2021)
The traumas often involve the maxillofacial area, but stab wounds to the face are rare. The protective defense mechanism activates instinctively defending the face from any possible injuries. Due this lower incidence and also the various forms of injuries and objects used for such injury, stab wounds become a challenge for surgeons. The surgeon must be completely familiar and prepared to meet this demand on the emergency room. The purpose of this paper is to report a case of aggression with bladed weapon. The trauma generated by a member of his family against a woman caused an injury in the left infraorbital region, transfixing until the region of hard palate, where it was possible to see the end of the knife. A surgical procedure was performed under general anesthesia to remove the foreign body and synthesize the tissues. The patient recovered well, without any more serious complications, only with paraesthesia of the left infraorbital nerve. The patient remained in follow-up for two months and did not attend the other appointments for a long-term evaluation.